Ultrasonographic Assessment of Renal Parameters in Apparently Healthy Medical Students of A University Hospital - Thapa, Sushma; Khanal, Ujjwal P; Paudel, Sharma; Sigdel, Mahesh R (Journal of Institute of Medicine Nepal, 2023)
Introduction Ultrasonography is a commonly used medical imaging technique to evaluate the kidneys and has become the preferred modality for the assessment of renal pathology. However, limited data are available on the normal renal parameters in Nepalese adults. The aim of this study was to establish normal reference ranges for renal size in healthy medical students using ultrasonography. Methods A total of 100 healthy undergraduate medical students (64 males; 36 females) between the first and internship years (age 19-29 years) were studied. Ultrasonography was performed using a single and specific ultrasound machine with 1-7MHz transducer. Results The study showed the left kidney was slightly longer than the right (10.46 ± 0.68cm vs 10.13 ± 0.65cm; p=0.04), but the right kidney had a significantly larger thickness (2.80 ± 0.76cm vs 2.99 ± 0.68cm; p=0.01) and volume. A strong positive correlation was found between the renal parameters of one side with another side (Length: r=0.63,p<0.001; Breadth: r=0.42, p<0.001; Thickness: r=0.51, p<001; Volume: r=0.57, p<0.001). There were significant differences in renal length and volume based on sex, height, weight, and body mass index while other parameters were not significant. Weight was found to affect renal length more than height. Conclusion The left kidney was slightly longer than the right kidney. There was a strong positive correlation between the right and left kidney parameters. The study also found significant associations between renal length and height, weight, and body mass index.